Hubungan Tingkat Pendidikan Formal dengan Tingkat Pengetahuan Wanita tentang Kanker Payudara - Faija Sihombing (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2020)
Breast cancer is a that is often found in indonesian sosiety and occupy the second place most after cervical cancer. The fact that occurs,the magnitude of death due to cancer due to late check into health facilities or patients come at an advanced stage. The higher the level of formal education more easily absorb information as well as health information, the higher the awareness to behave healthy life. The purpose of this study is to find out how the relationship or formal education with the level of knowledge of women about breast cancer in Harjosari Village II Medan Amplas District. The method used by writer is observasional and done by cross sectional. All members of the population were taken as a sample of 98 people. Data collection tool used in this research is questionnaire in the form of multiple choice. The analytical technique used in descriptive and inferential at 95% confidence level and proccessed with SPSS program version 16.00 from the result of statistical analysis obtained the value of Rho ±0.318 and significance value p=0,000 which means the value p<o.oo5. The conclusion of this study is that there is a significant possitive relationship between the level of formal education with the level of knowledge of women in Harjosari Village II Medan Amplas District. The higher the level of women’s education the better the knowledge about breast cancer, otherwise the lower the education of women the less knowledge about breast cancer.